Pengaruh penambahan auxin terhadap pertunasan dan perakaran kopi arabika perbanyakan Somatic Embryogenesis (The effects of shooting and rooting of arabica coffee propagation through Embryogenesis Somatic auxin uses). - Rina Arimarsetiowati; Fitria Ardiyani (Indonesian Coffee and Cocoa Research Institute, 2012)
Plantlet that has developed shoots and roots will have a high level adaptation in the field. The objective of this experiment was to improve the ability of planlet in shooting and rooting so that it is ready for acclimatization in the field. The increase ability in shooting and rooting of the planlet were conducted by adding various types of auxin in the media. The arabica coffee embryo of clone AS 2K which has entered the phase of the cotyledons was transfered into the treatment media containing half-strength of MS (Murashige & Skoog) macro and micro nutrient, vitamin B5, 30 g/L glucose, 100 ml/L coconut water, 50 mg/L AgNO3 added with the combination of IAA, IBA and NAA. The research was conducted by using completely randomized design with seven combined treatment i.e. 0.1 mg/L IBA, 0.1 mg/L NAA, 0.1 mg/L IAA; 0 , 1 mg/L IBA + 0.1 mg/L NAA, 0.1 mg/L IBA + 0.1 mg/L IAA, 0.1 mg/L NAA + 0.1 mg/L IAA; without auxin. There were 12 replications in every treatment and each replication consisted of five cotyledonary embryos. The parameters of observation were the root length, leaf number, leaf area, stem diameter, and height of plantlets. The observations were conducted in eighth weeks after cotyledonary embryo had shoots. The results showed that in the number of leaves and height of planlet parameters, the treatment without auxin was the best result compared to planlet with auxin addition. The addition of auxin varians and their combination did not significantly influent leaf area, root length and stem diameter parameters. The medium tested was optimum for the growth of shoots and roots of AS 2K arabica coffee.